Workplace Spirituality and Employee Well-Being: The Mediating Roles of Mindfulness and Workforce Agility - Viona Thalita; Achmad Sudiro; Noermijati Noermijati (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This article investigates whether workplace spirituality shapes employee well-being among hybrid creative-economy workers in DKI Jakarta, while positioning mindfulness and workforce agility as the intervening mechanisms. Design/methodology/approach – The research applied a quantitative explanatory approach. Survey responses were obtained online from 225 purposively selected employees, and the proposed model was tested with Partial Least Squares Structural Equation Modeling (PLS-SEM). Finding/Results – The analysis shows that workplace spirituality has no statistically meaningful direct effect on employee well-being. However, it significantly strengthens mindfulness and workforce agility; in turn, both variables improve employee well-being. These results indicate that mindfulness and workforce agility fully channel the influence of workplace spirituality on employee well-being. Originality/Value – From a theoretical standpoint, the article extends discussion of employee well-being by highlighting psychological awareness and adaptive capability within creative-economy work. For practice, the results can inform organizational programs aimed at sustaining employee well-being in hybrid settings.